INTERRELATION OF INDICATORS OF BODY COMPOSITION WITH THE EFFECTIVENESS OF COMPETITIVE ACTIVITY OF HIGHLY QUALIFIED BIATHLETES - Zagursky, N.S.; Romanova, Ya.S. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the relationship between the body composition of highly qualified biathletes and the indicators of competitive activity at the stages of long-term training. Methods and structure of the study. The scientific work was carried out with the participation of biathletes of the qualification Master of Sports, Master of Sports of International Class and Honored Master of Sports in the sports seasons of 2015-2022. Bioelectrical impedance analysis (BIA) was carried out on a Maltron Bioscan 920-II using the equations for the European population with the choice of the level of sports fitness - "Athlete". Results and conclusions. Monitoring of changes in body composition using BIA Maltron BioScan 920-II and caliperometry allows you to assess current and cumulative changes in the process of long-term training of biathletes with high accuracy and reliability. Using the BIA Maltron BioScan 920-II allows you to obtain indicators that are not available using the caliperometry method. As a result of the analysis, indicators of body composition were identified that can be successfully used in monitoring body composition under the influence of training and competitive loads. The highest relationship among the analyzed indicators of body composition with the speed of movement along the distance has the sum of fat folds and the percentage of adipose tissue (R=0.44-0.51 at P>0.05). An increase in the loss to the leader in terms of movement speed was recorded with a decrease in the content of intracellular water in the body (ICW), protein, potassium, glycogen, percentage of adipose tissue, an increase in the content of extracellular water in the body (ECW) and total body water (TBW).